2014
DOI: 10.1111/anec.12138
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of Clinician ECG Interpretation for Athletes

Abstract: Clinician ECG interpretation according to the ESC interpretation criteria appears to demonstrate limited reliability and validity. Before widespread adoption of ECG for PPE of U.S. athletes, further research of training focused on improved reliability and validity of clinician ECG interpretation is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…Lever et al [28] reported that only 11% of final--year medical students and resident medical officers accurately recognized the WPW-syndrome pattern. The results are consistent with a growing literature suggesting that non-cardiologists often have difficulties in interpreting ECG tracings [29]. The present study indicates that Emergency Department staff needs a special training in rare but potentially lethal arrhythmias as the misinterpretation of tachycardia etiology may result in adverse outcome [25][26][27].…”
Section: Discussionsupporting
confidence: 91%
“…Lever et al [28] reported that only 11% of final--year medical students and resident medical officers accurately recognized the WPW-syndrome pattern. The results are consistent with a growing literature suggesting that non-cardiologists often have difficulties in interpreting ECG tracings [29]. The present study indicates that Emergency Department staff needs a special training in rare but potentially lethal arrhythmias as the misinterpretation of tachycardia etiology may result in adverse outcome [25][26][27].…”
Section: Discussionsupporting
confidence: 91%
“…Some studies have demonstrated that systematic evaluation of an athlete's ECG using standardised criteria improves interpretation accuracy 89 90. However, interobserver variability and the reliability of ECG standards even among experienced physicians remains a major concern 91 92. In one study, paediatric cardiologists, without the use of a standardised criteria set, achieved a sensitivity of 68% and a specificity of 70% for recognition of abnormal ECG patterns that occur infrequently, but may represent conditions predisposing to SCD 93…”
Section: Ecg For the Cardiovascular Screening Of Athletesmentioning
confidence: 99%
“…By using the Seattle criteria, the number of "abnormal" ECGs appears to be the smallest and there is less need for further diagnostic evaluation [6,24]. When the 2010 ESC guidelines were used, there were no differences in sensitivity and specificity in detection of abnormal ECG patterns between cardiologists and primary care specialists; however, cardiologists did, with significantly greater sensitivity, correctly diagnose the abnormal patterns [4,13].…”
Section: Pre-participation Cardiovascular Screening Protocolsmentioning
confidence: 99%
“…The incidence of SCDs in athletes under 35 years of age is between 0.4 in 100,000 in Italy, and 4.4 in 100,000 in the United States of America (USA), but it can be as high as 6 in 100,000 [2][3][4][5][6][7]. SCD death rate among athletes who are members of the National Collegiate Athletic Association (NCAA) was found to be 2.3 in 100,000 [8].…”
Section: Introductionmentioning
confidence: 99%